KONTRIBUSI MAá¸¤FÅªáº’ AL-TARMASÄª DALAM PENGKAJIAN HADIS DI INDONESIA - Faisal, Ahmad (Department of Hadis Sciences (IH), Faculty of Usuluddin, Adab, and Da'wah (FUAD), State Islamic Institute of Langsa (IAIN), 2018)
Modern Had?? experts are still very minimal, even there are still many mu?addi? figures who are not yet known by the public. One of them was Shaykh Mu?ammad Ma?f?? ibn Abdull?h ibn Abd alMann?n al-Tarmas? al-J?w? al-Makk? al-Sy?fi??. Shaykh Mu?ammad Ma?fu? compiled the book of Jurisprudence and Proposals, Had?? and also al-Qir??at. The contribution of Ma?f?? al-Tarmas?'s thoughts in the study of Had?? in Indonesia can be seen in the book, first; Al-Min?ah al-Khairiyyah. Second, Manhaj ?aw? al-Na?ar f? Syar? Man??mati ?Ilm al-?A?ar. Third, Transmission of Sanad in the book entitled Kif?yatu al-Mustaf?d f?m? ?al? min al-As?n?d by the work of Muhammad Y?sin alF?n?n?. Ma?fu? al-Tarmas?'s work entitled Manhaj ?aw? al-Na?ar f? Syar? Man?umati ?Ilm al-?A?ar is a book that is used as a reference in many universities such as Egypt, Morocco, Mecca and Indonesia. This one work is the explaination book from the great work of the world Had?? scholars, namely Alfiyyah al-Suy??? who discusses the science of Had??. The difficulty in understanding the na?m-na?m contained in the work of al-Suy???, makes Ma?fu? al-Tarmas? challenged and then agrees with it with the intention to be more easily understood and understood by students and lovers of Had?? knowledge in general.